Faktor-Faktor yang Mempengaruhi Kinerja Keuangan UMKM di Wilayah 3T (Terdepan, Terluar, dan Tertinggal): Peran Moderasi Literasi Keuangan - Michael Miran; Lenny Leorina Evinita; Pricilia Joice Pesak (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
This study investigates the factors influencing the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia's 3T regions—lagging (tertinggal), frontier (terdepan), and outermost (terluar)—with financial literacy positioned as a moderating variable. Despite playing a crucial role in driving local economic growth, MSMEs in 3T areas face persistent challenges such as limited market access, inadequate infrastructure, and a shortage of skilled human resources. The study focuses on internal perspective factors, the use of accounting applications, and marketplace platforms as potential determinants of financial performance. Using a quantitative approach, a survey was conducted among MSME actors in Bitung City, a designated 3T area. The data were analyzed using SmartPLS regression. The findings indicate that accounting applications alone do not significantly enhance financial performance without sufficient financial literacy. Conversely, marketplace utilization substantially improves performance by expanding market reach and boosting sales. Internal perspectives show limited influence unless supported by training or external assistance. Although financial literacy does not statistically moderate the relationships tested, practical experience emerges as a critical component. The study underscores the importance of combining digital tools, experiential learning, and institutional support to strengthen the financial performance of MSMEs in remote and underserved regions.